Portomesenteric venous gas: A late complication of pneumatosis intestinalis - Faraj, W. (Int J Surg Case Rep, 2014)
BACKGROUND: The pneumatosis intestinalis is an entity with multiple aetiologies and may be associated with a fatal outcome when present on plain radiographs. When associated with the presence of portomesenteric venous gas (PMVG) it is typically the result of bowel ischaemia. METHODS AND RESULTS: We are presenting a case of a 43 year old male who presented with a two days history of haematemesis, generalised abdominal pain and distension. Computed tomography (CT) scan revealed a gross amount of air within the portal venous system and small bowel dilatation to the level of distal ileum was also seen with associated pneumatosis intestinalis. Emergency laparotomy was conducted which demonstrated a simple band adhesion resulting in bowel ischaemia. The patient was making a good post-operative recovery complicated only by sub-therapeutic treatment of schizophrenia. CONCLUSION: The presence of gas within the portal venous system and PI in adults can indicate severe life-threatening disease. This requires early surgical intervention in those patients with a clinical suspicion of bowel ischaemia, and with radiological signs. This may avoid significant mortality.